Plant-Based Antioxidants for Prevention and Treatment of Neurodegenerative Diseases: Phytotherapeutic Potential of Laurus nobilis, Aronia melanocarpa, and Celastrol - Kristina Pilipović; Renata Jurišić Grubešić; Petra Dolenec; Natalia Kučić; Lea Juretić; Jasenka Mršić-Pelčić (MDPI AG, 2023)
With the progress of medicine, especially in the last century, life expectancy increased considerably. As a result, age-related diseases also increased, especially malignancies and degenerative diseases of the central nervous system. The incidence and prevalence of neurodegenerative diseases steadily increased over the years, but despite efforts to uncover the pathophysiological processes behind these conditions, they remain elusive. Among the many theories, oxidative stress was proposed to be involved in neurodegenerative processes and to play an important role in the morbidity and progression of various neurodegenerative disorders. Accordingly, a number of studies discovered the potential of natural plant constituents to have significant antioxidant activity. This review focused on several plant-based antioxidants that showed promising results in the prevention and treatment of neurodegenerative diseases. Laurus nobilis, Aronia melanocarpa, and celastrol, a chemical compound isolated from the root extracts of Tripterygium wilfordii and T. regelii, are all known to be rich in antioxidant polyphenols.